The Peroxisome Proliferator-Activated Receptor Gamma System Regulates Ultraviolet B-Induced Prostaglandin E2 Production in Human Epidermal Keratinocytes. (26th April 2010) - Konger, Raymond L.; Martel, Kellie Clay; Jernigan, Danielle; Zhang, Qiwei; Travers, Jeffrey B.
Abstract : Studies using PPARγ agonists in mouse skin have suggested that peroxisome proliferator-activated receptor gamma (PPARγ ) is irrelevant to cutaneous photobiology. However, in several epithelial cell lines, ultraviolet B (UVB) has been shown to induce the nonenzymatic production of oxidized phospholipids that act as PPARγ agonists. UVB is also a potent inducer of prostaglandinE 2 ( PGE 2 ) production and COX-2 expression in keratinocytes and PPARγ is coupled to increasedPGE 2 production in other cell lines. In this current study, we demonstrate that PPARγ agonists, but not PPARα or PPARβ / δ agonists, inducePGE 2 production and COX-2 expression in primary human keratinocytes (PHKs). Importantly, PPARγ agonist-induced COX-2 expression andPGE 2 production were partially inhibited by the PPARγ antagonist, GW9662, indicating that both PPARγ -dependent and -independent pathways are likely involved. GW9662 also suppressed UVB and tert -butylhydroperoxide- (TBH-) inducedPGE 2 production in PHKs and intact human epidermis and partially inhibited UVB-induced COX-2 expression in PHKs. These findings provide evidence that PPARγ is relevant to cutaneous photobiology in human epidermis.